2019
DOI: 10.1039/c8ra10171j
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of vanadium-containing silica SBA-3 materials and their catalytic activity for propene oxidation

Abstract: Efficient SBA-3 vanadosilicate catalysts for propene oxidation obtained for the first time by the one-pot synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…The band at approximately 250 nm can be assigned to highly dispersed, isolated tetrahedral vanadium species combined with oxygen atoms from tetrahedral silica. The band located at 290 nm corresponds to isolated tetrahedral vanadium species on the surface of the silica walls [40–42] . Furthermore, the other absorption peaks at approximately 320 and 390 nm suggest the presence of a fraction of aggregated VO x [43,44] .…”
Section: Resultsmentioning
confidence: 97%
“…The band at approximately 250 nm can be assigned to highly dispersed, isolated tetrahedral vanadium species combined with oxygen atoms from tetrahedral silica. The band located at 290 nm corresponds to isolated tetrahedral vanadium species on the surface of the silica walls [40–42] . Furthermore, the other absorption peaks at approximately 320 and 390 nm suggest the presence of a fraction of aggregated VO x [43,44] .…”
Section: Resultsmentioning
confidence: 97%
“…These results contradict our previous ndings for vanadosilicates of SBA-3 structure. 22 The VSBA-3 catalysts showed higher TOF values for low vanadium content (<1 wt%), which suggested that some vanadium species do not show activity in epoxide formation. This could result from the relatively narrow pore system of VSBA-3 causing some diffusion limitation.…”
Section: Catalytic Performance For Propene Epoxidationmentioning
confidence: 94%
“…20,21 Recently, vanadosilicates of SBA-3 structure have been successfully explored in propene epoxidation with N 2 O. 22 Based on the high catalytic activity of vanadium-supported MCF materials in propene epoxidation by N 2 O, in the present study, we report the preparation and catalytic performance of mesoporous vanadosilicates of 3D mesopore systems, namely, KIT-6, SBA-12, and MCF, synthesized by direct one-pot pH adjustment method. MCF, SBA-12, and KIT-6 have a threedimensional pore architecture which, in principle, enables facile transport of reactant and product molecules and access to active sites.…”
Section: Introductionmentioning
confidence: 96%
“…While there has been research on non-noble metal based catalysts, their practical use remains constrained by various challenges, including challenging disposal methods, elevated toxicity, and reduced activity levels. [14][15][16][17][18][19] On the other hand, choosing an appropriate catalyst for green oxidative removal of BTEX pollutants has remained a considerable challenge. Owing to the abundance of released petroleum scraps in the environment, the oxidative transformation reactions have to be aerobic or oxygen-induced with minimum energy and chemical consumption, but there are only a few reports that introduce the ideal protocol.…”
Section: Introductionmentioning
confidence: 99%